english english - Noviyanti, Ririn; Albab, M. Ulil (University of Darusssalam Gontor, 2023)
Halal lifestyle has recently begun to be hotly discussed. Both by halal lifestyle activists and the community as producers and consumers. The 2018 Halal Economy and Strategy Roadmap states that Indonesia's total consumption of halal goods and services in 2017 was around US 218,8 billion. This number is estimated to continue to grow by an average of 5,3% and reach US 330,5 billion in 2025. This has also received appreciation and support by LPPOM-MUI by holding a Halal Award on July 7, 2022 ago. This study aims to analyze in depth about the potential of halal lifestyle influencers in their efforts to educate and socialize netizens about halal lifestyle, especially on Muslim Indonesia. This type of research was qualitative with a netnography approach. Netnography is a method used to uncover and analyze publicly available information where everyone is free to share through social media networks. Netnography can be defined as a research method within the network, an adaptation of ethnography applied to understand social interactions in the context of digital communication. Observations and documentation were used as data collection techniques. Meanwhile, data analysis uses data content analysis. This research found that halal lifestyle enthusiasts through halal content become one of the important agents in the context of disseminating halal information and knowledge and become a trigger in uploading halal awareness. Involving halal lifestyle enthusiasts has great potential and can have a positive impact on halal socialization in Indonesia. The contribution of this research was to provide a concrete picture regarding the role of halal lifestyle influencer in increasing the awareness of halal lifestyle in Indonesia.